2022
DOI: 10.1038/s41598-022-05370-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of size on InGaN red micro-LEDs

Abstract: In this research, five sizes (100 × 100, 75 × 75, 50 × 50, 25 × 25, 10 × 10 µm2) of InGaN red micro-light emitting diode (LED) dies are produced using laser-based direct writing and maskless technology. It is observed that with increasing injection current, the smaller the size of the micro-LED, the more obvious the blue shift of the emission wavelength. When the injection current is increased from 0.1 to 1 mA, the emission wavelength of the 10 × 10 μm2 micro-LED is shifted from 617.15 to 576.87 nm. The obviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 20 publications
(30 reference statements)
3
51
1
Order By: Relevance
“…The same group investigated the effect of size on the emission wavelength and injection current of μLEDs. With the decrease in size, the injection current increased and there was a blue shift in the emission wavelength . In 2021, Lau et al also reported AlGaInP-based red AM microdisplays with Au/In flip-chip bonding technology …”
Section: Overview Of μLedsmentioning
confidence: 99%
See 4 more Smart Citations
“…The same group investigated the effect of size on the emission wavelength and injection current of μLEDs. With the decrease in size, the injection current increased and there was a blue shift in the emission wavelength . In 2021, Lau et al also reported AlGaInP-based red AM microdisplays with Au/In flip-chip bonding technology …”
Section: Overview Of μLedsmentioning
confidence: 99%
“…In 2022, Horng's team fabricated and analyzed red InGaN μLEDs of different sizes. 46 The team used the laser direct writing exposure technology to perform a maskless patterning process for μLEDs in different sizes (100 × 100, 75 × 75, 50 × 50, 25 × 25, and 10 × 10 μm 2 ). The sidewall damage from dry etching was effectively fixed with a SiO 2 passivation layer implemented by plasma-accelerated chemical vapor deposition (PECVD).…”
Section: ■ Monochromatic μLedsmentioning
confidence: 99%
See 3 more Smart Citations